Exploring the Contingent Role of Effort Expectancy on Online Purchase Intention in E-commerce Application - Lydia Ery Octalina; Anni Rahimah; Zainul Arifin (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study examines the influence of hedonic and utilitarian values on perceived benefits and their impact on purchase intention by using effort expectancy as a moderating variable. Design/Methods/Approach: This study adopts a quantitative approach by employing a non-probability sampling technique to collect a sample of 175 respondents who had used the Shopee application in Malang. The data was analyzed using SmartPLS through the measurement model test (outer model) and structural model test. Findings: The results show that hedonic value and utilitarian value have a positive and significant effect on perceived benefit, hedonic value and utilitarian value have a positive and significant impact on purchase intention, and perceived benefit has a positive and significant effect on purchase intention. However, effort expectancy does not have a significant role in moderating the relationships. Originality/Value: The limited extant literature only addresses a simple direct–effect relationship between effort expectancy toward behavioral intention and use behavior. Drawing on the Unified Theory of Acceptance and Use, this research provides deep insight through position effort expectance as the moderation role. Also, this study elaborates on the effect of utilitarian and hedonic values on perceived benefit. In turn, this framework also explored the influence of perceived benefit on consumer intention to purchase in electronic commerce, further advancing an understanding of this dynamic subject matter. Practical/Policy Implications: The study contributes to the existing knowledge of managerial practice by pointing out the importance of effort expectancy, which shapes the consumer's perceived benefit, and illustrating its impact in the case of purchasing intention in an e-commerce application. E-commerce companies can enhance the customer experience when accessing applications to invigorate purchase intention. E-commerce companies need to maintain their performance in terms of app ease of use and provide innovations by providing more user benefits, thereby creating loyal customers. Eventually, the company should keep earning society's trust as reliable e-commerce that meets the needs of today's digital era.